Islamic Art and the Museum: Approaches to Art and Archaeology of the Muslim World in the Twenty-First Century By Benoît Junod, Georges Khalil, Stefan Weber, and Gerhard Wolf, eds. (London: Saqi Books, 2012. 374 pages.) (American Journal of Islam and Society, 2014)
This volume contains an impressive number of essays by authors from diversebackgrounds. What the title does not indicate is the reason for this publication– the conference “Layers of Islamic Art and the Museum Context” (held inBerlin during January 13-16, 2010) in cooperation with the Aga Khan Trustfor Culture, the Museum of Islamic Art in Berlin, and the “Europe in the MiddleEast – The Middle East in Europe” (EUME). The EUME is a Berlin-basedresearch program initiated by the Brandenburg Academy of Science, the FritzThyssen Foundation, Wissenschaftskolleg zu Berlin, and the Forum TransregionaleStudien. This publication drew upon the expertise of the Aga KhanNetwork and experts in Germany because it was originally to be a workshopfocused on the reorganization of Berlin’s Museum of Islamic Art (MIA) aswell as a study for Toronto’s Museum of Islamic Art, which will open thisyear and house the Aga Khan’s personal collection.The forum offers a certain diversity of voices regarding issues in general(the display of Islamic art around the world) and specific to the MIA at thePergamon Museum. Its twenty-nine essays are divided into five sections: “In-132 The American Journal of Islamic Social Sciences 31:2troduction,” ...